2015
DOI: 10.1007/s10967-015-4461-2
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of radionuclides and metals to graphene oxide and magnetic graphene oxide

Abstract: Graphene oxide (GO) and two magnetic graphene oxide (MGO) composites with a different amount of magnetite were synthesized, characterized and used in sorption experiments. The effect of pH on sorption of Am(III) and Pu(IV) isotopes as well as Co(II), Ni(II), Cu(II) and Pb(II) to GO and MGO was studied in equilibrium and kinetic experiments. The adsorption capacities varied from 30 to 574 mg g -1 while rate constants ranged from 0.29 to 0.46 min -1 and increased in the following order Co, Cu, Pb and Ni. Large v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…The Freundlich model assumes that the adsorption occurs in multiple layers (physical adsorption), within non-uniform sites, characteristic of heterogeneous systems. 43,51 Similar results are reported by Rhoden et al (2021) 18 by removing hydrochlorothiazide (HCTZ) from aqueous solutions by applying GO nanocomposites. The maximum adsorption capacity of GO was achieved at pH 7.0 (20.87 mg g −1 ), which corresponds to 52.97% of HCTZ removed from the aqueous medium.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The Freundlich model assumes that the adsorption occurs in multiple layers (physical adsorption), within non-uniform sites, characteristic of heterogeneous systems. 43,51 Similar results are reported by Rhoden et al (2021) 18 by removing hydrochlorothiazide (HCTZ) from aqueous solutions by applying GO nanocomposites. The maximum adsorption capacity of GO was achieved at pH 7.0 (20.87 mg g −1 ), which corresponds to 52.97% of HCTZ removed from the aqueous medium.…”
Section: Resultssupporting
confidence: 83%
“…41,42 In the XRD of the reduced graphene oxide, it is possible to identify the presence of a maximum diffraction peak at approximately 25.6°, due to the interlayer spacing decrease, referent to the removal of oxygenated groups by the ascorbic acid. 43…”
Section: Resultsmentioning
confidence: 99%
“…Moreover the 3D spongy structure greatly enhanced the surface area for the maximum adsorption of uranium ion. Study has shown that a higher level of GO oxidation facilitates higher loading of magnetite nanoparticles that ensures higher sorption sites for the uptake of metal ions and radionuclides from contaminated solution such as Cu 2+ , Co 2+ , Ni 2+ , Pb 2+ , Pu 4+ . Xue et al designed an electroresponsive hydrogel based upon the GO as backbone and redox active ruthenium complexes as noncovalent cross-linkers .…”
Section: Go For the Removal Of Metal Ions And Other Contaminants From...mentioning
confidence: 99%
“…As its derivative, graphene oxide (GO) exhibits superior properties. Both GO and graphene have two-dimensional, sheet-like structures which are connected by carbon atoms through the hybridization of sp 2 and σ bonds to the surrounding carbon atoms to form a hexagonal honeycomb lattice [2,3,4]. Compared with graphene, GO has a large number of oxygen-containing functional groups at the edges and inside of the sheet, including hydroxyl groups, carbonyl groups, carboxyl groups, and epoxy groups, which allows GO to be operatively bonded to organic pollutants [5,6,7].…”
Section: Introductionmentioning
confidence: 99%